Pengaruh Penilaian dan Pencatatan Prestasi terhadap Pembentukan Sikap Disiplin Siswa SD - Hanadea Juwita; Jefrison Bili; Nesya Aprilianingrum; Octavia Ayu Ramadhani; Lisa Virdinarti Putra (Yayasan Literasi Sains Indonesia, 2025)
Character education serves as a crucial foundation for shaping a generation that excels not only academically but also in personality. One of the key attitudes that must be instilled early is discipline. In this context, student assessment and performance recording are not merely tools to measure academic outcomes but also reflections of students' behavior and character development. When students realize that their attitudes and achievements are acknowledged and valued, they develop an intrinsic motivation to behave more responsibly. Field observations indicate that schools integrating positive behavior tracking into their evaluation systems tend to foster students who are more disciplined, more rule-conscious, and more engaged in school activities. Holistic assessment fosters a sense of fairness and intrinsic drive among students. Therefore, evaluation policies should not only focus on numerical scores but also emphasize and nurture character values. This approach is a strategic step toward strengthening character education through a structured and continuous system.